Indonesian Financial Service Authority as Sole Investigator in Eradication of Money Laundering - Kristian, Otniel Yustisia (Jurnal Mulawarman Law Review, 2024)
With the granting of authority for OJK as sole investigator of criminal acts in the financial services sector as specified in Law Number 4 Year 2023, it is necessary to analyze its implications for the investigation of money laundering crimes, this is because criminal acts in the financial services sector is predicate crime of money laundering. Another thing that needs to be analyzed is whether the provision in the P2SK Law that authorizes OJK as the sole investigator of criminal acts in the financial services sector can be applied, because there is PP No. 55 of 2023 which also authorizes Police Investigators to conduct investigations in the financial services sector. The type of legal research is normative. Based on the research conducted, it is concluded that referring to the Stufenbau des Recht theory, in the event of a conflict between the provisions in the P2SK Law and the PP Regulation on Criminal Investigation in the Financial Services Sector can have consequences on the declared invalidity of the provisions regulated in the Government Regulation. Then, the implication of the granting of authority to OJK as the sole investigator in the financial services sector is that the implementation of Money Laundering investigations with criminal acts originating in the financial services sector can only be investigated by OJK. In addition, Analysis Results from PPATK which indicates criminal acts in the financial services sector can only be submitted to OJK.